Analysis of Human Resources Management Practices of Small and Medium Enterprises of Knowledge-based Industry in Bandung - Lathiva, Nurul; Febriansyah, Hary (Journal of Business and Management, 2020)
Abstract. Particularly for Small and Medium Enterprises (SMEs), which usually do not have a Human Resources Management department to rely on, HRM practices can be a challenge. They may be limited to one HR person or the CEO will still have the responsibility. SMEs owners need to consider the implementation and obstacles they face, however, so that they are prepared to address HR problems as their company and workforce expand. SMEs in Indonesia are currently taking advantage of a challenge into an attractive opportunity to encourage the growth of SMEs themselves. This research is to study SMEs in the knowledge based in Bandung in understanding what and how the HR practices in organizations, conducted in Bandung city by using the explanatory mixed method which consist of questionnaire for quantitative data and in-depth interviews for qualitative data collection. The respondents from questionnaire consist of 25 representative of SMEs knowledge-based industry, and the informants taken in the interview were 5 representative of SMEs knowledge-based industry who included from 25 respondents from questionnaire. When analyzing data, descriptive statistics are used for quantitative purposes and backed up by cross-case analysis to concentrate on comparing and integrating statements from each question provided to all interview informants when order to obtain athorough understanding of HRM implementation practices in knowledge-based SME industries. Based on this study, implementation of HRM practices by formal and informal institutions can change organizations, HRM activity activities significantly influence the results of business operations. Keywords: Human Resources Management Practices, Small and Medium Enterprises (SMEs), knowledge-based industry.